2015
DOI: 10.1016/j.cct.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary lifestyle intervention for weight management in a community population (HealthTrack study): Study design and baseline sample characteristics

Abstract: (2015). Interdisciplinary lifestyle intervention for weight management in a community population (HealthTrack study): study design and baseline sample characteristics. Contemporary Clinical Trials, 45 (Part B), 394-403.Interdisciplinary lifestyle intervention for weight management in a community population (HealthTrack study): study design and baseline sample characteristics AbstractBackground Integrating professional expertise in diet, exercise and behavioural support may provide more effective preventive hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 40 publications
(32 reference statements)
0
32
0
Order By: Relevance
“…The detailed study protocol is described elsewhere [24]. In brief, the study recruited adults 25-54 years of age through advertisements in local newspapers Individuals who could not communicate in English, had severe medical conditions that limited their ability to participate in the study, immunodeficiency, had medical conditions that could limit survival to 1 year, reported excessive alcohol intakes (greater than 50 grams of alcohol per day) or illegal drug use, or had difficulties in participating in some parts of the study were excluded.…”
Section: Study Context: the Healthtrack Studymentioning
confidence: 99%
“…The detailed study protocol is described elsewhere [24]. In brief, the study recruited adults 25-54 years of age through advertisements in local newspapers Individuals who could not communicate in English, had severe medical conditions that limited their ability to participate in the study, immunodeficiency, had medical conditions that could limit survival to 1 year, reported excessive alcohol intakes (greater than 50 grams of alcohol per day) or illegal drug use, or had difficulties in participating in some parts of the study were excluded.…”
Section: Study Context: the Healthtrack Studymentioning
confidence: 99%
“…To the authors' knowledge, this study is the first to develop an AUSNUT Golley et al, 2015;Louie et al, 2015;Meng et al, 2010;Neale et al, 2013;Tapsell et al, 2014;Waern et al, 2015;Wood et al, 2014), including in recent research such as the HealthTrack study (Tapsell et al, 2015). This was despite the database being developed in line with a survey food.…”
Section: Discussionmentioning
confidence: 99%
“…AUSNUT 1999 and Government Department of Health and Ageing, 2008). Until the release of AUSNUT 2011-13, AUSNUT 2007 was the most timely food composition survey database available in Australia, and has been widely applied in nutrition research (Elliott et al, 2014;Golley et al, 2015;Louie et al, 2015;Meng et al, 2010;Neale et al, 2013;Tapsell et al, 2014;Tapsell et al, 2015;Waern et al, 2015;Wood et al, 2014).…”
Section: Databases In the Ausnut Series Include Ausnut 1999 (Food Stamentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed study protocol is reported elsewhere [14]. In brief, the HealthTrack study enrolled adults aged between 25 and 54 years recruited through advertisements in local newspapers from the Illawarra community, a major coastal region 70 km south of Sydney, Australia.…”
Section: Study Context: the Healthtrack Trialmentioning
confidence: 99%